Enhancing surface oxygen retention through theory-guided doping selection in Li1−xNiO2 for next-generation lithium-ion batteries. Issue 44 (23rd October 2020) - Cheng, Jianli; Mu, Linqin; Wang, Chunyang; Yang, Zhijie; Xin, Huolin L.; Lin, Feng; Persson, Kristin A.
Abstract : Using a collaborated in silico and experimental approach, we designed Sb-doped LiNiO2 with improved surface oxygen retention and electrochemical performance. Abstract : Layered lithium metal oxides have become the cathode of choice for state-of-the-art Li-ion batteries (LIBs), particularly those with high Ni content. However, the Ni-rich cathode materials suffer from extensive oxygen evolution, which contributes to the formation of surface rocksalt phases as well as thermal instability. Using first-principles calculations, we systematically evaluate the effectiveness of doping elements to enhance surface oxygen retention of Li1− x NiO2 . The evaluation process includes (i) choosing the most stable surface facet from the perspective of equilibrium surface stability analysis of as-synthesized LiNiO2, (ii) determining the preferable atomic site and segregation behavior for each dopant, and (iii) evaluating the surface oxygen retention ability of doped-Li1− x NiO2 (0.25 ≤ x ≤ 1) compared to the pristine material. We also discuss and rationalize the ability of these elements to enhance surface oxygen retention based on local environment descriptors such as dopant–oxygen bond strength. Overall, W, Sb, Ta and Ti are predicted as the most promising surface dopants due to their strong oxygen bonds and robust surface segregation behavior. Finally, Sb-doped LiNiO2 is synthesized and shown to present a surface enrichment of Sb and a significantly improved electrochemical performance, comparing with pristine LiNiO2 . This work provides a generic approach that can lead to the greatly enhanced stabilization of all high-energy cathode materials, particularly the high Ni and low Co oxides.